Efficient and Scalable Syntheses of 1,2-Thiaselenane-4-amine and 1,2-Thiaselenane-5-amine - Zeisel, Lukas; Maier, Martin S.; Thorn-Seshold, Oliver (Synthesis, 2023)
The first regioselective syntheses of 1,2-thiaselenane-4-amine (TSA4) and 1,2-thiaselenane-5-amine (TSA5) are developed. Both are redox motifs with high value in chemical biology that until now were hindered by tedious synthesis. An aziridine intermediate and a kinetically controlled S-acylation were leveraged for regioselective chalcogen installations. Short, fast sequences were optimised with just one or two chromatographic steps that cheaply deliver these motifs on scale for high throughput inhibitor screening, and thus provide a robust methodology for assembling other selenenyl sulfides.
Keywords: redox; chemical probe; selenenyl sulfide; dichalcogenide; disulfide; fluorogenic probe; thioredoxin reductase; regioselective synthesis